Endothelial dysfunction in patients after COVID-19 - Gozhenko, A.; Kuznetsova, H.; Pavlega, O.; Ilyina-Stognienko, V.; Rusnak, S.; Zukow, W. (Journal of Education, Health and Sport, 2022)
Relevance: Over the past two years, the COVID-19 infection has gained unprecedented relevance at the global level. All countries are spending significant resources in the fight against COVID-19 [1 2]. The purpose of the work is to clarify the issue of the state of the kidneys in the distant post-covid period (after 2-3 months), we conducted a study of the kidneys simultaneously with the desquamation of the endothelium, as one of the probable mechanisms of the nephrotic effect of the COVID-19 virus. Materials and methods: 29 people participated in the study. Patients with post-covid syndrome (n=10) were treated on an outpatient basis at the "KNP "Center of primary medical and sanitary (medical and sanitary) care No. 3, Odesa" of the Odesa City Council" in the period from 2020 to 2021. The control group consisted of patients without cardiovascular and endocrine disorders, comparable in terms of gender and age, who were examined in 2018 at the Odesa Regional Clinical Medical Center of the Odesa Regional Council. Endothelial dysfunction "ED" was determined by the intensity of desquamation of the endothelium according to the method of J. Hladovec as modified by M.M. Petryschev. and other. (2001). Statistical analysis was performed using Status software [https://status-please.herokuapp.com/]. Mean values ​​(M) and its standard deviation (SD) were used to describe quantitative data, and percentages were used for qualitative data. For comparison, data were presented as M and standard error of the mean (SEM). Analysis of normality was performed using the Shapiro-Wilk test. Levene's test was used to assess homogeneity of variances. Differences between groups were determined using Student's t-test and one-way analysis of variance (ANOVA). The relationship and presence of correlation between the studied parameters was determined using the Pearson correlation coefficient (r). The correlation coefficient in the range of 0.5≤|r|<1 indicated a strong correlation relationship, 0.3≤|r|<0.5 – a relationship of medium strength, 0<|r|<0.3 – on a weak correlation. Statistical significance was established only at the level of p < 0.05. Results: 17 men and 12 women aged from 32 to 80 years who suffered from a disease of moderate severity participated in the study. The average age of the group of patients with post-covid syndrome (n=9) is 55.9±14.47 years, the average age of the control group (n=20) is 55.95±14.47 years. There were no complaints from the urinary system in the examined patients. According to blood serum tests, it was established that the creatinine level among patients with post-covid syndrome was on average 113±11.91 μmol/l, the urea level was 8.11±1.2 mmol/l, the GFR level was 55.06±12, 19 ml/min/1.73. m2. In the control group, the numbers were as follows: creatinine level was 73.2±8.5 μmol/l, mean urea level was 4.61 mmol/l, GFR was 94.78±13.76 ml/min/1.73 m2. Conclusions: 2-3 months after the transfer of COVID-19, the examined patients show signs of chronic kidney disease. After a disease with COVID-19, an increase in CEC is detected, which is a manifestation of endothelial dysfunction.